1993
DOI: 10.1007/bf00234500
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dietary phosphorus-dependent duodenal calcium uptake in vitamin D-deficient chicks

Abstract: The effect of dietary phosphorus on intestinal calcium uptake was examined in duodenal cells isolated from vitamin D-deficient chicks. Cells from chicks on a high phosphorus diet accumulated calcium at a rate 38% higher than cells from animals on a normal phosphorus diet. Diet high in calcium did not affect calcium absorption in duodenal cells. The dietary phosphorus effect on calcium absorption was specific. Uptake of alpha-methyl glucose was not altered. Increase in calcium absorption by a high phosphorus di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Whether this is a transient non-steady-state phenomenon, secondary to changes in intestinal transit time, or an indirect effect mediated via higher rates of production of 1,25 (OH ) 2 vitamin D 3 and increased active intestinal absorption of calcium, requires further study. Previous studies have shown that reduction of phosphate in a diet decreases the PTH level and increases the 1,25(OH) 2 vitamin D 3 level [18][19][20][21]. Moreover, these studies revealed an increased calcium excretion in the urine, an increased intestinal calcium absorption and occasionally an increase in the total ionized serum calcium.…”
Section: Discussionmentioning
confidence: 96%
“…Whether this is a transient non-steady-state phenomenon, secondary to changes in intestinal transit time, or an indirect effect mediated via higher rates of production of 1,25 (OH ) 2 vitamin D 3 and increased active intestinal absorption of calcium, requires further study. Previous studies have shown that reduction of phosphate in a diet decreases the PTH level and increases the 1,25(OH) 2 vitamin D 3 level [18][19][20][21]. Moreover, these studies revealed an increased calcium excretion in the urine, an increased intestinal calcium absorption and occasionally an increase in the total ionized serum calcium.…”
Section: Discussionmentioning
confidence: 96%